2017
DOI: 10.1016/s0140-6736(16)30677-8
|View full text |Cite|
|
Sign up to set email alerts
|

Acute myocardial infarction

Abstract: Acute myocardial infarction has traditionally been divided into ST elevation or non-ST elevation myocardial infarction; however, therapies are similar between the two, and the overall management of acute myocardial infarction can be reviewed for simplicity. Acute myocardial infarction remains a leading cause of morbidity and mortality worldwide, despite substantial improvements in prognosis over the past decade. The progress is a result of several major trends, including improvements in risk stratification, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
687
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,011 publications
(765 citation statements)
references
References 139 publications
2
687
0
18
Order By: Relevance
“…Acute myocardial infarction (AMI) is one of the most severe manifestations of coronary artery diseases that causes irreversible damage to the heart muscle, and can lead to development of heart failure [1, 2]. AMI leads to more than 4 million deaths in Europe and northern Asia [3].…”
Section: Introductionmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) is one of the most severe manifestations of coronary artery diseases that causes irreversible damage to the heart muscle, and can lead to development of heart failure [1, 2]. AMI leads to more than 4 million deaths in Europe and northern Asia [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in the treatment of ST‐segment–elevation myocardial infarction (STEMI) have resulted in improved outcomes over the past 2 decades 1, 2. However, STEMI remains a significant cause of morbidity and mortality in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial ischemia/reperfusion injury is one of the most common causes of death worldwide [1][2][3][4][5][6]. Numerous studies have demonstrated that cell death is an important component in the pathogenesis of various cardiac diseases, including heart failure, myocardial infarction (MI) and ischemia/reperfusion (I/R) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%